2020
DOI: 10.1186/s12891-020-03663-x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of fetal skeletal dysplasia using 3-dimensional computed tomography: a prospective study

Abstract: Background Fetal skeletal dysplasia (FSD) comprises a complex group of systemic bone and cartilage disorders. Many FSD phenotypes have indistinct definitions, making definitive prenatal diagnosis difficult. The condition is typically diagnosed using sonography; however, three-dimensional computed tomography (3D-CT) also aids in making a prenatal diagnosis. This study aimed to examine the efficacy of 3D-CT in the prenatal diagnosis of FSD by comparing the diagnostic accuracy of fetal sonography and 3D-CT. Met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In another study, 3D-CT was performed on 19 foetuses with suspected skeletal dysplasia; the diagnosis was confirmed in 17 of them, including three with OI. In their study, 3D-HCT showed 100% sensitivity, specificity, and positive and negative predictive values, while sonography alone had sensitivity, specificity, and positive and negative predictive values of 100%, 85%, 89.5%, and 100%, respectively [ 48 ].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, 3D-CT was performed on 19 foetuses with suspected skeletal dysplasia; the diagnosis was confirmed in 17 of them, including three with OI. In their study, 3D-HCT showed 100% sensitivity, specificity, and positive and negative predictive values, while sonography alone had sensitivity, specificity, and positive and negative predictive values of 100%, 85%, 89.5%, and 100%, respectively [ 48 ].…”
Section: Diagnosismentioning
confidence: 99%
“…According to the International Commission of Radiological Protection, foetal radiation exposure of less than 100 mGy would have no practical significance and will not increase lifetime cancer risk [ 49 ]. The dose for 3D-HCT was a mean computed tomography dose index (CTDIvol) of 3.5 mGy, which is far below the 100 mGy limit [ 48 ]. Overall, 3D-HCT would be a valuable tool for the prenatal diagnosis of skeletal dysplasia, including OI.…”
Section: Diagnosismentioning
confidence: 99%
“…In the 2015Nosology and Classification of Genetic Skeletal Disorders (GSDs) there were 436 GSDs with hundreds of causative genes (Bonafe et al, 2015). Fetal skeletal dysplasia (FSD) comprises a complex group of systemic bone and cartilage disorders (Waratani et al, 2020).…”
Section: Journal Of Clinical Orthopaedics and Trauma Carementioning
confidence: 99%
“…Fetal skeletal dysplasia is a disease with generalized abnormalities of the skeleton, affecting approximately 2–5 of 10,000 births 1,2 . At present, the prenatal diagnosis of fetal skeletal dysplasia mostly relies on ultrasound, X‐ray, and magnetic resonance imaging 3–6 . On ultrasound, in the second and third trimesters, fetal skeletal dysplasia is primarily characterized by shortened long bones, narrow thorax, abnormal head shape, and polyhydramnios 7 .…”
mentioning
confidence: 99%
“…1,2 At present, the prenatal diagnosis of fetal skeletal dysplasia mostly relies on ultrasound, X-ray, and magnetic resonance imaging. [3][4][5][6] On ultrasound, in the second and third trimesters, fetal skeletal dysplasia is primarily characterized by shortened long bones, narrow thorax, abnormal head shape, and polyhydramnios. 7 As with all other serious congenital anomalies, it is important to diagnose this condition as early as possible during pregnancy.…”
mentioning
confidence: 99%